Expression of pattern recognition receptors and activation of the non-canonical inflammasome pathway in brain pericytes - Nyúl-Tóth Ádám (BRAIN BEHAVIOR AND IMMUNITY, 2017)
Cerebral pericytes are mural cells embedded in the basement membrane of capillaries. Increasing evidence suggests that they play important role in controlling neurovascular functions, i.e. cerebral blood flow, angiogenesis and permeability of the blood-brain barrier. These cells can also influence neuroinflammation which is highly regulated by the innate immune system. Therefore, we systematically tested the pattern recognition receptor expression of brain pericytes. We detected expression of NOD1, NOD2, NLRC5, NLRP1-3, NLRP5, NLRP9, NLRP10 and NLRX mRNA in non-treated cells. Among the ten known human TLRs, TLR2, TLR4, TLR5, TLR6 and TLR10 were found to be expressed. Inflammatory mediators induced the expression of NLRA, NLRC4 and TLR9 and increased the levels of NOD2, TLR2, inflammasome-forming caspases and inflammasome-cleaved interleukins. Oxidative stress, on the other hand, upregulated expression of TLR10 and NLRP9. Activation of selected pattern recognition receptors can lead to inflammasome assembly and caspase-dependent secretion of IL-1beta. TNF-alpha and IFN-gamma increased the levels of pro-IL-1beta and pro-caspase-1 proteins; however, no canonical activation of NLRP1, NLRP2, NLRP3 or NLRC4 inflammasomes could be observed in human brain vascular pericytes. On the other hand, we could demonstrate secretion of active IL-1beta in response to non-canonical inflammasome activation, i.e. intracellular LPS or infection with E. coli bacteria. Our in vitro results indicate that pericytes might have an important regulatory role in neuroinflammation.